Modeling of electric MHD flow of nanoparticles in a CMC-water based casson hybrid nanofluid over a porous medium - Alkasasbeh, Hamzeh Taha; Hanandeh, Feras A.; Aljunaeidia, Bajes Z.; Al-Olaimat, Nesreen M.; Alzyout, Abduallah M.; Khalil, Sara A.; Muhammad Khairul Anuar, Mohamed (Semarak Ilmu Publishing, 2024)
The principal focus of this exploration is to study the computationally simulate the combined convection of CMC-water-based Casson hybrid nanofluid through a stretching sheet with electric magnetic force in a porous medium. Copper (Cu) and Silver (Ag) nanoparticles are included to enhance the heat transfer performance of CMC-water. The physical problem is formulated with mathematical PDEs, and to solve this, initially we used similarity transformation technique to reduce the PDEs into ODEs, then Runge-Kutta Fehlberg method (RKFM) of order four with shooting technique is adopted for further reduction from the non-linear ODEs to first order DEs. The influence of key parameters such as the magnetic field parameter (M), porous medium parameters (K), electric field factor (E), radiation parameter (Nr), permeability parameter (λ), Casson parameter (β), and Eckert number (Ec) on relevant physical quantities is illustrated through tables and graphical visualizations. The impact of these parameters on velocity and temperature profiles, as well as on the skin friction coefficient and Nusselt number of the nanofluid, is observed. Our results indicate that an increase in the Casson parameter values leads to a decrease in the velocity of the host fluid in the case of opposite flow, and a similar behavior is observed with the nanoparticle porous medium parameter (K) in the case of assisting flow. Furthermore, the use of the Runge-Kutta Fehlberg Method (RKFM) is found to be more accurate and reliable in dealing with the problem studied in this work.